Frontal and temporal contributions to understanding the iconic co‐speech gestures that accompany speech. Issue 3 (14th December 2012) - Dick, Anthony Steven; Mok, Eva H.; Beharelle, Anjali Raja; Goldin‐Meadow, Susan; Small, Steven L.
<x xml:space="preserve">Abstract</x> In everyday conversation, listeners often rely on a speaker's gestures to clarify any ambiguities in the verbal message. Using fMRI during naturalistic story comprehension, we examined which brain regions in the listener are sensitive to speakers' iconic gestures. We focused on iconic gestures that contribute information not found in the speaker's talk, compared with those that convey information redundant with the speaker's talk. We found that three regions—left inferior frontal gyrus triangular (IFGTr) and opercular (IFGOp) portions, and left posterior middle temporal gyrus (MTGp)—responded more strongly when gestures added information to nonspecific language, compared with when they conveyed the same information in more specific language; in other words, when gesture disambiguated speech as opposed to reinforced it. An increased BOLD response was not found in these regions when the nonspecific language was produced without gesture, suggesting that IFGTr, IFGOp, and MTGp are involved in integrating semantic information across gesture and speech. In addition, we found that activity in the posterior superior temporal sulcus (STSp), previously thought to be involved in gesture‐speech integration, was not sensitive to the gesture‐speech relation. Together, these findings clarify the neurobiology of gesture‐speech integration and contribute to an emerging picture of how listeners glean meaning from gestures that accompany speech. Hum Brain Mapp 35:900–917, 2014. © 2012 Wiley Periodicals, Inc.